Molecular Pathology Protocols - Killeen, Anthony A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2001)
Because molecular pathology has only recently emerged from the laboratory, many molecular pathology protocols are still to be found only in the primary literature. In Molecular Pathology Protocols, Anthony Killeen has assembled a collection of readily reproducible molecular pathology techniques that are either frequently performed or recognized for their significant diagnostic utility. Each method is described in step-by-step detail by a leading molecular pathologist or laboratory scientist who has developed it or used it extensively. These clinical laboratory techniques can be used for the diagnosis or monitoring of cancer, hematological malignancies, infectious diseases, and selected genetic disorders. Cutting-edge methods include telomerase, microsatellite instability, chromosomal translocations, and fluorescent in situ hybridization assays. Time-tested practices and numerous tips on how to avoid pitfalls ensure robust and successful results. Comprehensive and path-breaking, Molecular Pathology Protocols will enable clinical laboratories to introduce new molecular pathology tests and lay the groundwork for a much-needed standardization in this rapidly developing field.
DNA Extraction from Paraffin-Embedded Tissues -- DNA Extraction from Fresh or Frozen Tissues -- RNA Extraction from Fresh or Frozen Tissues -- Single-Strand Conformation Polymorphism Analysis of Mutations in Exons 4-8 of the TP53 Gene -- Cleavase® Fragment Length Polymorphism Analysis for Genotyping and Mutation Detection -- Detection of Telomerase by In Situ Hybridization and by the Polymerase Chain Reaction-Based Telomerase Activity Assay -- Detection of Microsatellite Instability -- Polymerase Chain Reaction Clonality Assays Based on X-Linked Genes -- Fluorescent In Situ Hybridization -- HER-2/neu Oncogene Amplification Determined by Fluorescence In Situ Hybridization -- A Nested Reverse Transcription-Polymerase Chain Reaction Assay to Detect BCR/abl -- Detection of t(15;17)(q24;q21), inv(16)/t(16;16)(p13;q22), and t(8;21)(q22;q22) Anomalies in Acute Myeloid Leukemias -- Detection of t(14; 18)(q32;q21)-Associated BCL-2/JH Gene Fusion in Non-Hodgkin Lymphoma -- Detection of Breast Cancer Cells Using Immunomagnetic Beads and Reverse Transcriptase Polymerase Chain Reaction -- Molecular Detection of Circulating Prostate Cancer Cells -- Methods to Detect Clonal Gene Rearrangements in Lymphomas and Leukemias -- Monitoring of Bone Marrow Transplant Engraftment -- Direct Molecular Diagnosis of Multiple Endocrine Neoplasia Type 1 -- Molecular Detection of Multiple Endocrine Neoplasia Type 2 -- Assay for Detecting the I1307K Susceptibility Allele within the Adenomatous Polyposis ColiGene -- Detection of Human Papillomaviruses by Polymerase Chain Reaction and In Situ Hybridization -- Molecular Methods for Detecting Epstein-Barr Virus (Part I) -- Molecular Methods for Detecting Epstein-Barr Virus (Part II) -- Molecular Methods for Detecting Epstein-Barr Virus (Part III) -- Molecular Detection of Kaposi’s Sarcoma-Associated Herpesvirus/ Human Herpesvirus-8 -- Diagnostic Applications of Quantitative Polymerase Chain Reaction for Cytomegalovirus -- A Colorimetric Microtiter Plate Polymerase Chain Reaction System That Detects Herpes Simplex Virus in Cerebrospinal Fluid and Discriminates Genotypes 1 and 2 -- Detection and Typing of Hepatitis C Virus -- Detection and Speciation of Mycobacteria in Formalin-Fixed, Paraffin-Embedded Tissue Sections -- Ultrasensitive Quantitation of Human Immunodeficiency Virus Type 1 RNA in Plasma by the AMPLICOR and COBAS AMPLICOR HIV-1 MONITOR™ Tests -- Molecular Diagnosis of Hereditary Thrombotic Disorders -- Prenatal Genotyping of the RhD Locus to Identify Fetuses at Risk for Hemolytic Disease of the Newborn -- Molecular Diagnosis of Hereditary Hemochromatosis -- Genotyping of Apolipoprotein E -- Genotyping for Functionally Important Human CYP2D6*4 (B) Mutation Using TaqMan Probes.
Keywords: Pathology; Pathology